2020
DOI: 10.18632/aging.103292
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the association between nut consumption and the risks of cancer incidence and cancer-specific mortality

Abstract: Previous studies have indicated a correlation between nut intake and cancer risk in humans. This meta-analysis aimed to determine the relationship between nut consumption and the risks of cancer incidence and mortality. The PubMed, Embase, and Web of Science databases were searched up to August 2019. Relative risks and 95% confidence intervals were calculated using random-effects and fixed-effects models. We included 38 studies on nut consumption and cancer risk and 9 studies on cancer-specific mortality. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 57 publications
(84 reference statements)
2
31
0
Order By: Relevance
“…In the case of cashew nut-based products, around 50% of their weight were cashews, being the major ingredient, followed by water and lemon juice. The health benefits of whole nuts consumption is well-known [ 33 , 34 ], and it has been reported that other nut-based processed products, such as peanut butter without added sugars, could provide some health benefits, reducing the risk of type 2 diabetes incidence [ 35 ]. In the case of tofu-based products, 98.5% of the products’ weight is soy milk.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of cashew nut-based products, around 50% of their weight were cashews, being the major ingredient, followed by water and lemon juice. The health benefits of whole nuts consumption is well-known [ 33 , 34 ], and it has been reported that other nut-based processed products, such as peanut butter without added sugars, could provide some health benefits, reducing the risk of type 2 diabetes incidence [ 35 ]. In the case of tofu-based products, 98.5% of the products’ weight is soy milk.…”
Section: Discussionmentioning
confidence: 99%
“…These sex-differentiated associations could be due to chance. Four meta-analyses have suggested the protective effect of nut intake on cancer mortality (8,9,11,12) . However, one of the four meta-analyses that combined four cohorts in Europe and the USA presented no evidence for heterogeneity in the associations between men and women (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the nutritional perspective, previous studies suggested that nut intake was associated with glucose and blood lipid control, and modulation of inflammation, oxidative stress, endothelial function and insulin resistance (2)(3)(4)(5)(6) . Through these mechanisms, nut intake may contribute to preventing cardiovascular diseases (CVDs) and other chronic diseases (7)(8)(9)(10)(11)(12) . Although peanuts are legumes, they are treated as nuts because their nutrient contents are similar to those of almonds and other tree nuts (6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other studies have evaluated the relationship between nut consumption and risk of cancer mortality. An earlier meta-analysis by Zhang et al in 2020 showed that total nut consumption was associated with a reduced odds ratio (OR) of cancer-related mortality (OR = 0.90; 95% CI, 0.88, 0.92) [ 48 ]. In this meta-analysis, statistically significant inverse associations between nut consumption and cancer site occurrence were present for colorectum, stomach, pancreas, and lung.…”
Section: Nut Consumption and Health Outcomesmentioning
confidence: 99%